Peran Pemerintah Daerah Dalam Mendorong Desa Berdaya Saing Berdasarkan Undang-Undang Desa - Memorianus Amazihono; Gede Wijaya Kusuma; Susiana Setianingsih (Departement of Mathematics Education, 2024)
The classic problem of villages in almost all of Indonesia is that human resources are less competent in managing the village so that the potential natural resources cannot be managed by the village but are controlled by parties outside the village. The solution to this problem is that there must be integrated programs, systems, policies, rules and laws from the central government, regional governments at the provincial, district and city levels. UU no. 6 of 2014 concerning villages is expected to be a historical milestone for the creation of prosperous and competitive villages. A competitive village is a village that is prosperous, can develop its village potential and provide welfare to the village community. Villages are the backbone of the country's economy. However, the current condition is that villages are unable to compete with big cities in terms of the economy because lack of access to resources, limited infrastructure, and lack of job opportunities are often the main obstacles in creating competitive villages. Therefore, it is quite important for local governments to encourage village potential so that they can compete and manage the village's natural resource potential in accordance with the mandate of the village law..